On the shop floor two studies of workshop organization and output. - Lupton, Tom (International Series of monographs on social and behavioral sciences, 1963)
On the Shop Floor: Two Studies of Workshop Organization and Output is an empirical study of the social factors influencing output in factories. The book investigates the correlation between worker social behavior and production output levels. The text presents a firsthand account of the social behavior of workers in two separate and unrelated workshops. Technological and administrative controls, social structure, and resolution of conflicts in the workshops are analyzed. The book also considers output performance of individual workers involving case studies of factors influencing performance.